Poctory, Android Based Online History Card Game with NFC, GPS, and Internet Technology - Sulisthio, William Febrianto; Andjarwirawan, Justinus; Satiabudhi, Gregorius (Jurnal Infra, 2014)
Poctory is an Android based card game application which is based on history as its theme. Nowadays, there exist many card games created for Android, but there are not any that are based on Indonesian history or, use NFC and GPS technology. With regards to those problems, this thesis will make a card game application with Indonesian history as its theme, using NFC Technology for building deck of cards and battle matchmaking, also using GPS to pinpoint historical places.Important features in Poctory for instance the use of NFCÂ to determine deck of cards that are used by players, battle matchmaking using Android Beam, and pinpointing historical places using GPS. Client-side application is developed using Eclipse with Android Development Tools Plugin and SQLite, while its server-side is developed using PHP and MySQL.Based on the tests conducted, Poctory have achieved its purpose to facilitate learning history, made learning history more exhilarating, and also have a uniqueness if compared to other similar application.